NEW RECORDS OF MESOCYCLOPS GRANULATUS (DUSSART & FERNANDO, 1988) AND THERMOCYCLOPS MAHEENSIS (LINDBERG, 1941) COPEPODA: CYCLOPOIDA FROM FRESHWATER PONDS OF KERALA, INDIA - S, Resmi; Jayachandran, K.V. (Journal of Indian Fisheries Association, 2014)
Kerala state has a rich source of freshwater and it supports a high density of copepod diversity. From here, 4 genera and 12 species of cyclopoid copepod have been recorded so far and of which Mesocyclops and Thermocyclops dominate. Recently, Mesocyclops granulates (Dussart & Fernando, 1988) and Thermocyclops maheensis (Lindberg, 1941) have been collected and the present paper provides a detailed description of the two species as well as reports their new distributional rang. Mesocyclops granulates has been recordd from Faisalabad (Pakistan), Soqotra Island, Bangladesh, Burma and India (Meerut, Uttar Pradesh). Third segment of antennae of females of this species from Kerala with 7 setae is in contrast to 9 setae reported for Bangladesh population. Transverse ducts meeting at straight angle in Kerala Population while it forms ‘V’ shape in Bangladesh population. Thermocyclops maheensis has been recorded from Mahe (Pondicherry), Mysore (Karanataka), Thailand and Cambodia. The medial expansion of the basipodite is pilose on P1-P3 and bare on P4 in both Cambodian and Kerala females whereas in Maysore population, the basipodite is pilose on P1 and bare on P2-P4. Spinules on the posterior margin of anal somite usually absent, however, Kerala specimens sometimes possess 2 or 3 and that of Cambodian females with 9 or 10 spinules. Tips of S2 caudal setae are slightly curved in Kerala females while it varies from straight to strongly curved in the Cambodian females. Key words: Mesocyclops granulates, Thermocyclops maheensis, Kerala.